Lymphoepithelial Carcinoma of the Parotid: A Case Report and Review of the Literature. Issue 5 (September 2021) - Felicelli, Christopher; Alexiev, Borislav; Samant, Sandeep; Johnson, Daniel
Abstract : Abstract: Lymphoepithelial carcinoma (LEC) is an incredibly rare entity, accounting for less than 0.5% of all salivary gland malignancies. We present a case of a Southeast Asian women who presented with a rapidly enlarging parotid mass causing compressive symptoms. Surgical resection revealed nests of EBV-in situ hybridization positive pleomorphic cells surroundded by a dense lymphoplasmacytic infiltrate, consistent with LEC. The differential diagnosis and literature surrounding this rare entity is discussed.